KNOWLEDGE, ATTITUDES AND COMPLIANCE PRACTICE OF NURSES AND TECHNICIANS IN FLEXIBLE ENDOSCOPE REPROCESSING AND RELATED FACTORS AT VIETNAM NATIONAL CHILDREN'S HOSPITAL IN 2026 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the knowledge and attitudes regarding flexible endoscope reprocessing compliance among nurses and technicians, and to identify influencing factors at the National Children’s Hospital in 2026.Methods: A cross-sectional study using a mixed-methods approach (quantitative and qualitative). Data were collected from all nurses and technicians directly involved in endoscope reprocessing at the Endoscopy Departments (Gastroenterology and Respiratory), supplemented by in-depth interviews and focus group discussions.Results: Mean knowledge score was 78.4 ± 8.5%; 95.0% achieved Good and Average. Positive attitudes were found in 80.0% of staff. Key factors affecting compliance included: a shortage of dedicated reprocessing staff, exposure to toxic chemicals during manual cleaning, the absence of point-of-use cleaning verification tests, and inconsistent periodic monitoring.Conclusion: Mean knowledge score was 78.4 ± 8.5% with positive attitudes in 80.0% of staff. The study recommends increasing dedicated reprocessing personnel, investing in automated endoscope reprocessors (AERs), improving ventilation systems, and implementing rapid cleaning validation tools.
Keywords: Knowledge – Attitudes, flexible endoscope, instrument reprocessing, infection control, nurse, Vietnam National Children's Hospital